PROBLEM OF DRINKING WATER SUPPLY IN THE MUNICIPALITY OF BANIKOARA - Yetongnon, Judith Eric Georges (My University, 2020)
Most developing countries face enormous problems in accessing drinking water and managing water infrastructure. This study aims to analyze the problem of drinking water supply in the Municipality of Banikoara. To achieve this, a methodological approach focused on data collection, processing and analysis of results was adopted. A set of methods such as observation, field survey, analysis of water samples, and statistical treatments which have obtained the different results. From the analysis of the results, it emerges that modern wells, AEVs, FPMs are the main sources of access to drinking water in the Municipality. These structures serve the populations with a service rate of 35% which is below the rural rate which in fact 69%. Insufficient water points force people to obtain supplies from various sources of safe water. Likewise, access to drinking water is confronted with other factors which are: the accessibility to drinking water, measured by the type of supply, the distance and the cost of the purchase, seems to make account of the different methods of access to drinking water. Faced with these problems, it is imperative to review the methods of water management in the Municipality.
Keywords: Problematic; Supply; drinking water; Municipality of Banikoara